THE EFFECT OF LEADERSHIP STYLE, WORK MOTIVATION AND WORK DISCIPLINE ON THE PERFORMANCE OF EMPLOYEES AT THE KUKUH VILLAGE OFFICE KERAMBITAN DISTRICT, TABANAN REGENCY - Ni Made Sukerti; M. Rudi Irwansyah; I Nengah Suarmanayasa (RADJA PUBLIKA, 2026)
This study aims to describe the magnitude of the determination of several variables, namely: To analyze the influence of leadership style, work motivation and work discipline on employee performance at the Kukuh Village Office, Kerambitan District, Tabanan Regency. The population in this study were 37 employees of the Kukuh Village Office, Kerambitan District, Tabanan Regency. The sample determination in this study used a census technique. Data in this study were collected using observation and questionnaires. Data were analyzed using multiple linear regression tests. The results of the study indicate that: 1) Leadership style, work motivation and work discipline have a positive and significant effect on employee performance at the Kukuh Village Office, Keerambitan District, Tabanan Regency, 2) Leadership style has a positive and significant effect on employee performance at the Kukuh Village Office, Kerambitan District, Tabanan Regency, 3) Work motivation has a positive and significant effect on employee performance at the Kukuh Village Office, Kerambitan District, Tabanan Regency, 4) Work discipline has a positive and significant effect on employee performance at the Kukuh Village Office, Kerambitan District, Tabanan Regency. From the results of the multiple determination test, the R2 value is 0.680, which means that 68.0% of the proportion of variation (rise and fall) in employee performance at the Kukuh Village Office, Kerambitan District, Tabanan Regency can be explained by the proportion of variation (rise and fall) in the variables of leadership style, work motivation and work discipline, while the remaining 32.0% is explained by other variables not included in this research model.